The effect of Heating Temperature and Storage Time on Changes in Quality of Arenga pinnata Sap - Riko Saputra Jaya; Sentosa Ginting; Ridwansyah Ridwansyah (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The research was conducted to determine the effect of heating temperature and storage time (10 ºC) on changes of quality of Arenga pinnata sap. The research had been performed using a completely randomized design with two factors, i.e. heating temperature (S) : (without heating), (63 ºC), (90 ºC), (121 ºC) and storage time (L) : (0, 4, 8, and 12 days). Parameters analyzed were pH, total acid, total sugars, total soluble solid (TSS), total microbial, and sensory characteristics (color, aromatic, and taste) of the sap.The results showed that the heating temperature had highly significant effect on all parameters. Storage time had highly significant effect on all parameters. Interaction of both factors had highly significant effect on pH, total sugars, TSS, total microbial, sensory characteristics (color, aromatic, and taste) and had no significant effect on total acid of the sap. Heating temperature 121 ºC gave the best value for the quality of Arenga pinnata. Keywords : Arenga pinnata sap, heating temperature, and storage time.